Hair Restoration Surgery in Asians - Pathomvanich, Damkerng; Imagawa, Kenichiro; SpringerLink (Online service) (Tokyo : Springer Japan, 2010)
Hair transplantation is in demand worldwide, but because Asian hair tends to be more sparse and coarse than Caucasian hair, transplantation procedures need to be adapted to Asian patients. This book, exclusively devoted to Asian hair, is a complete and comprehensive text written by a group of authors sharing their experience in their specialized fields of hair restoration. Included are many practical tips as well as chapters on regional transplantation such as eyebrows, eyelashes, sideburns, beards, and mustaches, in addition to the usual scalp hair restoration. With its many illustrations, the book gives readers a complete knowledge of hair restoration surgery and provides a quick, easy-to-use reference on Asian hair and the differences in patients' demands. With an influx of new physicians in this challenging field of medicine, further education and training are imperative and must be available to provide a high standard of medical practice. This compilation meets that objective and ultimately makes the valuable contribution of restoring patients' self-confidence.
History and the Past -- Back to the Future: A Brief but Significant History of Hair Transplantation in Asians -- Asian Hair: Knowing the Differences -- The Prevalence of Male Pattern Baldness in Asian Men -- Knowing the Difference in Restoring the Asian Look -- Asian Hair: A Korean Study -- Consultation, Planning, and Hairline Design -- The Key to Success in Consultation -- Hair Restoration Surgery in Poor Candidates -- Preoperative Approach to Preexisting Scalp Lesions -- Planning for Ultra-Refined Follicular Unit Transplantation and the Hairline Design -- Laser-Assisted Rapid Hairline Placement -- When to Restore the Temple Area -- Crown: Area of Concern -- Should We Use Single or Multiple FU Grafts in Asians? -- Advantages of Microvascular Free Scalp Flap Transfer as a Means of Hair Transplantation -- Is There a Place for Scalp Flap in Modern Hair Restoration Surgery? -- Medical Treatment -- Medical Treatment of Hair Loss -- The Use of Herbal Medicine -- Is There a Place for Oral Minoxidil? An Overview -- Preoperative Care -- Preoperative Care for Super Mega-Sessions -- Local Anesthesia and Tumescence -- Safe Use of Local Anesthesia and Tumescence Fluid in the Donor Site as an Office-Based Procedure -- Preparing for a Painless Surgery: Medication or Meditation? -- Donor Harvesting -- Site Selection in Donor Harvesting: A Long and Winding Road -- The Strip: How Long, How Wide, and Where? -- A Refined Open Donor Harvesting to Minimize Follicular Transection -- Other Methods of Donor Harvesting -- Omnigraft$1!" (B-- Donor Wound Closure -- Donor Strip Removal and Wound Closure in Super Mega-Session: My Personal Technique -- Follicular Unit Extraction in the Asian Population -- Graft Preparation: Personal Techniques -- Slivering and Graft Cutting -- An Alternative Way of Graft Cutting -- Graft Dissection in Super Mega-Session: My Personal Technique -- Recipient Site Preparation and Insertion -- Dense Packing -- Premade Incisions: When and Where to Begin -- Why Lateral Slits? -- A Debate over Premade Incisions Versus (3z(BStick and Place(3y (B-- Technique of Fast and Efficient Graft Insertion -- Implanter -- Hair Restoration in Women and Transsexual Males -- Hair Restoration Surgery in Asian Women -- Hair Restoration Surgery in Transsexual Males -- Repairs: Personal Techniques -- Repair of Iatrogenic Scarring and Non-Scarring Alopecia from Cosmetic Surgery -- Cicatricial Alopecia in Hair Transplantation -- The Repair of Unwanted Plugs -- Repair of Scalp Flap -- Repair of Artificial Fiber Implantation -- Special Procedures in Hair Restoration Surgery -- Eyebrow Transplant -- Eyelash Transplant -- Sideburn Transplant -- Mustache Transplant -- Chest Hair Transplant -- Pubic Hair Transplant -- Postoperative Care -- Postoperative Care -- Postoperative Instruction Sheet Used in Our Clinic -- Complications -- Complications and the Solutions -- The Business Side -- Marketing and Management -- Hair Transplants in the Future -- Hair Cloning and Follicular Cell Implantation -- New Tools for Hair Transplants -- Application of Stem Cells in Hair Restoration Surgery.s
Keywords: Medicine; Dermatology; Surgery; Medicine & Public Health; Dermatology; Plastic Surgery